Chapter Верительная грамота Петра Первого в Светлейшую Республику в контексте российско-венецианских дипломатических отношений - KARDANOVA, NATALIYA (Biblioteca di Studi Slavistici, 2018)
In 1710-1711, at the time of preparation for the Prut campaign, Peter I sent three envoys to Venice, namely Urbich, Boris and Karetta. In 1716-1720, Becklemishev was appointed permanent Russuan economic representative in Venice. The article presents an analysis of credential letters of Peter the Great's envoys in Venice in connection with the pre-existing tradition and with due regard to the specifics of the Russian diplomatic ceremonial. The author aims to describe stylistic specifics of Peter I's credential letter and to determine its role for the subsequent tradition.